ANALISIS ANAK ANGKAT DALAM PERSPEKTIF HUKUM ISLAM, STATUS DAN KEDUDUKANNYA - Alang Sidek; Azhar Azhar; M. Habib (Prodi Hukum Ekonomi Syariah (Muamalah), 2018)
Adoption or adopting a child is still a polemic in its implementation, both under religious law and other laws. The purpose of this study is to clearly describe the status and position of adopted children, especially in the perspective of Islamic law. This type of qualitative research uses library research methods using secondary data in the form of books, journals and other scientific works. The findings in this study conclude that the position of adopted children according to the perspective of Islamic law is to remain as a legitimate child based on a court decision by not severing kinship / blood relations with their biological parents. While the status in inheritance for adopted children according to Islamic law is by way of grants and wills.